Neurocognitive benchmarks following transplant for emerging cerebral adrenoleukodystrophy. (4th August 2020) - Pierpont, Elizabeth I.; Nascene, David R.; Shanley, Ryan; Kenney-Jung, Daniel L.; Ziegler, Richard S.; Miller, Weston P.; Gupta, Ashish O.; Lund, Troy C.; Orchard, Paul J.; Eisengart, Julie B.
Abstract : Objective: To quantify benchmark treatment outcomes that may be enabled by newborn screening surveillance for X-linked adrenoleukodystrophy (ALD), we report neurocognitive, neuropsychiatric, and MRI change for boys who underwent hematopoietic stem cell transplant (HSCT) at initial stages of demyelination, prior to neurocognitive signs of disease. Methods: Retrospective chart review identified 36 patients whose cerebral ALD was detected and treated early, with lesion severity less than 5 on the ALD-specific MRI scoring system. Median age at transplant was 7.3 years (range, 4.0–16.1). Progression of radiologic disease on MRI in the 2 years following HSCT was examined relative to the severity of the initial lesion for 33 patients, and longitudinal neurocognitive and neuropsychiatric outcomes were studied for 30 patients. Results: Patients whose pretransplant lesion extended beyond the splenium of the corpus callosum and adjacent periventricular white matter (MRI severity score >2) demonstrated lower posttransplant neurocognitive scores, more neuropsychiatric symptoms, and more disease progression on MRI than patients with a less severe lesion. Changes from baseline neurocognitive functioning were greater at 2 years posttransplant as compared to 1 year. There was greater variance and risk of lesion progression as pretransplant MRI severity increased. Conclusion: To realize the full benefits of newborn screening, clinicians must detect very small demyelinating lesions during surveillance and intervene quickly. Novel interventions that reduce risks inherent in allogeneic transplantation are needed. Trial endpoints should include direct neurocognitive assessment and extend at least 2 years posttreatment to provide the greatest sensitivity to detect neurocognitive morbidity.